The Effect of Sharia Funds, E-Commerce, Online Financing, and Hedonism Lifestyle on Consumptive Behavior (Survey on SRB Mitra Agro Usaha Customers) - Novita, Dian; Sisdianto, Ersi; Selviana, Mia (Majapahit Journal of Islamic Finance and Management, 2025)
Consumptive behavior is an act of consumption that is carried out excessively and tends to be irrational, which can affect the financial condition of customers and the stability of bank financing. This study aims to analyze the consumptive behavior of customers at SRB Mitra Agro Usaha and the factors that influence it. The research method used is quantitative research method with structural equation model (SEM). The type of data used is the primary data in the form of questionnaires. The population in this study is the customer of SRB Mitra Agro Usaha. Sampling technique in this study using purposive sampling with the number of respondents as many as 100 respondents. The results of this study showed that Islamic funds have a negative and significant effect on customer consumptive behavior seen from the path coefficient value -0.187, t-statistic value 2.757 > t table 1.98 and p-value 0.006 < 0.05. E-commerce has a positive and significant effect on customer consumptive behavior seen from the path coefficient value of 0.483 t-statistic 5.444 > t table 1.98 and p-value 0.000 < 0.05. Online financing has a positive and significant effect on the customer's consumptive behavior seen from the path coefficient value of 0.285 t-statistic 3.317 > t table 1.98 and p-value 0.001 < 0.05 Hedonism lifestyle has a significant positive effect on the customer's consumptive behavior seen from the coefficient value of 0.358 t-statistic 3.881 > t table 1.98 and p-value 0.000 < 0.05. It can be concluded that Sharia funds have a negative and significant effect on consumptive behavior, while e-commerce, online financing, hedonism lifestyle have a positive and significant effect on customer consumptive behavior.